General Open Systems Theory and the Substrata-Factor Theory of Reading - Kling, Martin; International Reading Association, Newark, DE. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1966)
This study was designed to extend the generality of the Substrata-Factor Theory by two methods of investigation: (1) theoretically, to establish the validity of the hypothesis that an isomorphic relationship exists between the Substrata-Factor Theory and the General Open Systems Theory, and (2) experimentally, to discover through a series of substrata analyses the patterns of interaction by which a set of subject matter areas mutually and reciprocally support each other. Eight postulates, fundamental to both the General Open Systems Theory and the Substrata-Factor Theory, were identified. It was concluded (1) that there was an isomorphic relationship between all postulates in the two theories; (2) that subject matter areas could be conceived of as suprasystems girded by diverse, yet fundamentally related, subsystems; (3) that working system hierarchies were found for each content area manifesting quantitative and qualitative differences in organization of substrata sequences, amount of variance called for, and redundancy of particular variables; (4) that reciprocal interaction could be inferred from and X on Y and Y on X regression analysis; and (5) that the proration sequential technique might provide a basis for determining the extent of a particular subsystem's impact on the suprasystem. Suggestions for further research and a bibliography are included. (This document previously announced as ED 024 546.) (JB)
ERIC Note: Reprint from Highlights of the Pre-convention Institutes, 1965, Albert J. Kingston, Editor.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Models; Reading; Reading Processes; Systems Analysis; Systems Approach; Systems Concepts; Theories; Open Systems Theory -- Substrata Factor Theory